Effect of different viscous rejuvenators on chemical and mechanical behavior of aged and recovered bitumen from RAP. (10th April 2020) - Zhang, Jizhe; Sun, Changjun; Li, Peizhao; Jiang, Hongguang; Liang, Ming; Yao, Zhanyong; Zhang, Xiaomeng; Airey, Gordon
Highlights: Optimal viscosity of rejuvenator was effective to restore the tensile elongation and brittle fracture stress. Performance of rejuvenated binders strongly depended on the rejuvenator's viscosity. Rheological properties of aged bitumen are difficult to rehabilitate to exactly the same as that of the virgin bender. Abstract: Due to scarcity of virgin natural materials, the use of reclaimed asphalt pavement (RAP) has been promoted and encouraged in pavement engineering. However, note that the bituminous binder in RAP has been seriously aged due to long-term service exposure to the atmosphere. It is thus paramount to effectively restore properties of the RAP by adding proper rejuvenators. In this study, five rejuvenators were designed with different viscosities and applied to rejuvenate the aged binder. The changes in chemical compositions of bitumen caused by ageing and rejuvenating were evaluated by a SARA (Saturate, Aromatic, Resin and Asphaltene) analysis method. Brookfield viscosity, Dynamic Shear Rheometer (DSR) and Direct Tension (DT) were further conducted to evaluate the physical and mechanical properties of bituminous binders. Surface Free Energy test was applied to characterize the adhesion and moisture damage behavior of aged and rejuvenated binders. The experimental results showed that the ageing process increased resins and asphaltenes, which in turn improved the colloidal stability of the aged binder. The five rejuvenators designed in this research had a similar effect in restoring the rheological properties and stiffness of the aged bitumen to a similar level as that of the virgin binder. However, the viscosity level of rejuvenator has different impacts on tensile elongation at break, brittle fracture stress, adhesion property and moisture resistance of rejuvenated binders, in which the rejuvenator with an optimal viscosity may obtain the best rejuvenating performance.